Interface Engineering and Gate Dielectric Engineering for High Performance Ge MOSFETs - Jiabao Sun; Jiwu Lu (Advances in Condensed Matter Physics)
In recent years, germanium has attracted intensive interests for its promising applications in the microelectronics industry. However, to achieve high performance Ge channel devices, several critical issues still have to be addressed. Amongst them, a high quality gate stack, that is, a low defect interface layer and a dielectric layer, is of crucial importance. In this work, we first review the existing methods of interface engineering and gate dielectric engineering and then in more detail we discuss and compare three promising approaches (i.e., plasma postoxidation, high pressure oxidation, and ozone postoxidation). It has been confirmed that these approaches all can significantly improve the overall performance of the metal-oxide-semiconductor field effect transistor (MOSFET) device.